Foundations for Designing User-Centered Systems - Ritter, Frank E.; Baxter, Gordon D.; Churchill, Elizabeth F. (Springer, 2014)
Many books on user centered design and HCI focus on the way people interact with technology. This is an important issue, because people routinely interact with technology on a daily basis—personal computers, mobile phones, airplane cockpits, or even more mundane things like electric kettles and toasters. Despite everything that we know about interaction, however, technology still does not always support what we, as users, are trying to do, or behave in the way we expect it to. This can be exasperating for us: as users, as designers, and as developers. In Foundations for Designing User-Centered Systems we help you to understand why people behave and interact with technology in the way they do. By helping you understand both how and why people behave in the way they do, and by helping you to develop a more systems oriented perspective, we provide you with a framework that will enable you to develop technologies that are both useful and usable. These technologies will also be more acceptable to users because they will be better suited to the way users work in their normal environment.
What System Designers Need to Know about People